IMPLEMENTING PAIR WORK TECHNIQUE TO IMPROVE STUDENTS’ READING ABILITY ON DESCRIPTIVE TEXT AT THE ELEVENTH GRADE OF SMA NEGERI 1 AMANDRAYA - Laia, Temawanolo (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2022)
Reading is one of important skill of language for students. Based on the data obtained in preliminary study, some of the students of eleventh grade in SMA Negeri 1 Amandraya could not reach the Minimum Competence Criterion (MCC) of English subject which is 65 created by the school. This research was aimed at improving students’ reading ability on descriptive text by implementing Pair Work Technique. The subject of this research was 11th Grade which consisted of 22 students. The instruments of collecting the data were observation paper and test. This research conducted through classroom action research that consisted of two cycle. The result of the test in cycle I, students who passed was 9 or 41% while the students who failed was 13 or 59% with the average score was 63. Therefore, cycle I was unsuccessful, so the researcher continued in cycle II. In the cycle II, the students who passed was 18 or 82% while the students who failed was only 4 or 18% with the average score was 72. Based on the result of the research, it could be concluded that the students’ reading ability on descriptive text was improved through implementation of pair work technique, then the technique was applicable in teaching reading. Therefore, researcher suggested to the English teacher to apply Pair Work Technique in teaching reading, for the students, pair work technique is usefull and helpful in reading comprehension. It is expected that for the next researcher, this research can be a source or reference in doing research.